IL-17 inhibitor-associated inflammatory bowel disease: A study based on literature and database analysis - Deng, Zhenzhen; Wang, Shengfeng; Wu, Cuifang; Wang, Chunjiang (Frontiers in Pharmacology, 2023)
Objective: Few real-world studies have shown clear association between Interleukin (IL)-17 inhibitors and inflammatory bowel diseases (IBD) onset. This study aims to investigate the reporting prevalence as well as evaluate the clinical features and management of IL-17 inhibitors related IBD events. Methods: We used the US FDA Adverse Event Reporting System (FAERS) database and retrieved data during 2015-2022 of IL-17 inhibitors to identify gastrointestinal inflammatory events and conduct disproportionality analyses by estimating the reporting odds ratios (RORs) and corresponding 95% confidence intervals (CIs). Furthermore, case reports and case series from 2015 to November 30, 2022 on IBD induced by IL-17 inhibitors were collected for retrospective analysis. Results: A total of 388 cases of primary suspect IL-17 inhibitors associated gastrointestinal events was reported (268 IBD and 120 colitis), including 348 cases of Secukinumab (SEC), 36 cases of Ixekizumab (IXE), and 4 cases of Brodalumab (BRO). Statistically significant reporting rate of the total IBD events were observed for SEC and IXE (ROR=2.13, 95% CI [1.96-2.30] and ROR=2.79, 95% CI [2.39-3.27]), whereas BRO did not trigger signal. Twenty-nine studies with 34 cases raised evidence of IBD following SEC (79.4%) and IXE (20.6%) treatment. The median age was 42 years, typical initial symptoms included diarrhea (90.9%), abdominal pain (57.6%), bloody diarrhea (51.5%) and fever (36.4%). The median onset time of symptom was 2.9 months. Some cases were accompanied by elevated white blood cell account (WBC) (87.5%), erythrocyte sedimentation rate (ESR) (85.7%), C-reaction protein (CRP) (100%) and fecal calprotectin (FC) (100%). Cessation of IL-17 inhibitors with treatment of corticosteroids and anti- TNF antagonist monotherapy and combination therapy could lead to completely clinical remission. The median time of remission after IL-17 inhibitors discontinuation were 4 weeks. Conclusion: IL-17 inhibitors treatment is associated with exacerbations and new onset of IBD and colitis. Take a careful history before initiation of treatment and monitor of gastrointestinal symptoms and intestinal inflammatory biomarkers during ceasing of IL-17 inhibitors treatment is extremely important for their safety use.